Curso Modelado de Nicho Ecológico, Version 1.0 - Peterson, A. Townsend; Anderson, Robert P; Cobos, Marlon E; Cuahutle, Martín; Cuervo-Robayo, Angela P; Escobar, Luis E; Fernández, Marc; Jiménez-García, Daniel; Lira-Noriega, Andrés; Lobo, Jorge M; Machado-Stredel, Fernando; Martínez-Meyer, Enrique; et al. (Biodiversity Informatics, 2019)
The suite of ideas, protocols, and software tools that has come to be known as “Ecological Niche Modeling” (ENM) — as well as those for the related “Species Distribution Modeling” (SDM)—has seen intensive exploration and research attention in recent decades. In spite of at least four syntheses, the field has grown so much in complexity that it is rather difficult to access for newcomers. Until now, accessibility to this field was achieved by in-person courses organized by universities or research centers, in some of which we have participated as instructors. However, the access to these specialized courses is limited, on one hand because they are not offered in all universities, and on the other because normally they are taught in English. To expand the access to a wider community of Spanish-speaking researchers, here we offer an entirely digital and free-of-charge course in Spanish, which was presented over 23 weeks via Internet in 2018. Although intrinsic Internet-related barriers may limit access to course materials, we have made them available in diverse formats (video, audio, pdf) in order to eliminate most of these problems.